Complex metal mixture reduces apparent protein carbonylation in a tolerant aquatic macroinvertebrate, Arctopsyche grandis - Duggan, Sam B., author; Ramsdell, Howard, advisor; Clements, William, committee member; Legare, Marie, committee member (Colorado State University. Libraries, 2015)
Mining is widespread and an economically important industry. Unfortunately, acid mine drainage (AMD) can pollute ecosystems with a cocktail of contaminants too complex for accurately forecasting its health consequences. However, through quantification of fundamental toxic events, the effects of complex mixtures can be observed. This project explored two potentially insightful and convenient endpoints. First, oxygen consumption (MO2), a well-established and sensitive indicator of respiratory impairment was utilized. Second, protein carbonyl content (PCC), an experimental ecological biomarker widely lauded in biomedical circles as a highly conserved indicator of health status was assessed for its utility in a metal tolerant aquatic macroinvertebrate, Arctopsyche grandis. A. grandis were exposed to eight environmentally relevant target concentrations (in duplicate) of AMD for eight days at a temperature controlled greenhouse containing artificial flow-through streams. As expected, MO2 was inversely related to treatment concentration (R2=0.35, p=0.015). Protein carbonyl content, however, diverged from predictions. Protein carbonyl content analysis detected significantly more oxidative protein injury in control treatments than in metal-rich AMD treatments (p<0.001). Moreover, there was not a significant difference in PCC between different AMD concentrations. Protein carbonyl content's departure from anticipated results likely is the consequence of dynamic interactions between direct and indirect effects at the chemical, biochemical, physiologic and behavioral levels. The results of this project illustrate flaws of utilizing a single biochemical marker to observe effects of a toxic mixture. Rather, a broad suite of biomarkers should be assayed to determine sublethal toxicity. These results also illustrates how multiple stressors can yield unanticipated outcomes.